HISTORICAL TRUTH AND ITS IMPACT ON THE SPIRITUAL DEVELOPMENT OF SOCIETY (Scientific journal of the Fergana State University, 2023)
In this article the concept of historical truth, its structural system, its functions, historical and philosophical views on its realization, the relevance of the educational function of historical truth at a new stage of development, as well as the importance of historical truth in the spiritual life of society have been discussed.